Coaching agile teams a companion for ScrumMasters, agile coaches, and project managers in transition - Adkins, Lyssa (Pearson, 2024)
As an agile coach, you can help project teams become outstanding at agile, creating products that make them proud and helping organizations reap the powerful benefits of teams that deliver both innovation and excellence. More and more frequently, ScrumMasters and project managers are being asked to coach agile teams. But it's a challenging role. It requires new skills--as well as a subtle understanding of when to step in and when to step back. Migrating from "command and control" to agile coaching requires a whole new mind-set. In Coaching Agile Teams, Lyssa Adkins gives agile coaches the insights they need to adopt this new mind-set and to guide teams to extraordinary performance in a re-energized work environment. You'll gain a deep view into the role of the agile coach, discover what works and what doesn't, and learn how to adapt powerful skills from many allied disciplines, including the fields of professional coaching and mentoring. Coverage includes: Understanding what it takes to be a great agile coach Mastering all of the agile coach's roles (teacher, mentor, problem solver, conflict navigator, and performance coach) Creating an environment where self-organized, high-performance teams can emerge; coaching teams past cooperation and into full collaboration Evolving your leadership style as your team grows and changes Staying actively engaged without dominating your team and stunting its growth Recognizing failure, recovery, and success modes in your coaching Getting the most out of your own personal agile coaching journey Audiobook bonus content includes daily practices for getting present (Monday through Friday), and a Book Club Guide. Whether you're an agile coach, leader, trainer, mentor, facilitator, ScrumMaster, project manager, product owner, or team member, this audiobook will help you become skilled at helping others become truly great. What could possibly be more rewarding? Related Learning: Book: Coaching Agile Teams: A Companion for ScrumMasters, Agile Coaches, and Project Managers in Transition Video: Coaching Agile Teams Lyssa Adkins has taught Scrum to hundreds of students, coached many agile teams, and served as master coach to many apprentice coaches since 2004. Coaching coaches one-on-one and in small groups, she enjoys a front-row seat as remarkable agile coaches emerge and go on to entice the very best from the teams they coach. Prior to agile, Adkins had more than fifteen years of expertise leading project teams and groups of project managers in large and small consulting firms, commercial software companies, and the Fortune 500, yet nothing prepared her for the power of agile done simply and well. She teaches the "Coaching Agile Teams" training course, which allows agile coaches to learn, practice, and deepen the skills and mind-sets offered in the book. About Pearson Audio Learning Pearson publishes expert-led audio learning so you can dip into today's most important tech topics--wherever you are, wherever you go. Listen to industry leaders share first-hand experience, insights, and best practices using essential and emerging technologies.
Online resource; title from title details screen (O'Reilly, viewed February 19, 2024)
Keywords: Executive coaching; Teams in the workplace; Project management; Accompagnement de gestionnaires; Équipes de travail; Gestion de projet; Audiobooks; Livres audio